An equivalent beam approach for assessing tunnelling-induced distortions of frames with infills. (November 2022) - Franza, Andrea; Miraei, Seyedmohsen; Boldini, Daniela; Losacco, Nunzio
Highlights: Tunnelling-induced response of low- and medium-rise frames with infills is studied. Timoshenko beam founded on the half-space compared well with advanced simulations. Analytical approaches for the estimate of equivalent building stiffness are described. Angular distortion, corrected for the slab edge fixity, described well infill strains. A meta-model for predicting the angular distortion of frames is proposed. Abstract: This paper presents an approach to evaluate the response of low- and medium-rise frames with continuous foundations, either with or without infills, to tunnelling employing an equivalent beam with a behaviour dominated by shear deformations. Simplified soil-structure interaction models, consisting of a beam resting on an elastic continuum half-space, are compared against advanced three-dimensional analyses in which the tunnel, the soil, and the building are explicitly modelled. In the simplified approach, the frame is schematised as a Timoshenko beam and reliable procedures to estimate both bending and shear stiffness are discussed. In the refined modelling strategy, an advanced elastoplastic constitute law is employed, capable of reproducing fairly well the soil response to the excavation for increasing values of volume loss, while the full geometry of the structure is considered. First, the results of the proposed numerical approaches are compared in terms of tunnelling-induced foundation displacements, bay deformations and maximum tensile strains in the infills. Then, for the infill panels, the reliability of estimating the maximum tensile strain from the angular distortion of the frame bays is assessed. Finally, a meta-model is proposed to predict the maximum angular distortion based on greenfield settlements, eccentricity, and relative soil-structure stiffness.